The Aeneid of Virgil - Vandiver, Elizabeth, 1956-; Teaching Company (Springfield, VA : Teaching Co., 1999)
Presents Virgil's epic poem about Aeneas and his journey west from ruined Troy to the founding of a new nation in Italy. The Aeneid is an examination of leadership, a study of the conflict between duty and desire, a meditation on the relationship of the individual to society and of art to life, and a Roman's reflection on the dangers, and the allure, of Hellenistic culture. It represents both Virgil's tribute to Homer, and his attempt to re-imagine and surpass the Homeric model.
lecture 1. Introduction -- lecture 2. From Aeneas to Romulus -- lecture 3. Rome, Augustus, and Virgil -- lecture 4. The opening of the Aeneid -- lecture 5. From Troy to Carthage -- lecture 6. Unhappy Dido -- lecture 7. Funeral games and a journey to the dead -- lecture 8. Italy and the future -- lecture 9. Virgil's Iliad -- lecture 10. The inevitable doom of Turnus -- lecture 11. The gods and fate -- lecture 12. The end of the Aeneid and beyond.
Lecturer: Elizabeth Vandiver.
Compact discs.
In container (26 cm.).
Keywords: Virgil; Virgil -- Criticism and interpretation; Aeneas (Legendary character) in literature; Epic poetry, Latin -- History and criticism; Rome -- In literature